DEVELOPING CHARACTER-BASED ASSESSMENT IN TEACHING ENGLISH FOR THE TENTH GRADE STUDENTS OF SMKN 3 SINGARAJA - ., KOMANG AGUS OKA SAPUTRA; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA (Jurnal Pendidikan Bahasa Inggris, 2013)
This study was conducted by following the design of research and development model (R&D). The purposes of the study were: (1) To identify the problems faced by the English teachers in assessing students characters in SMKN 3 Singaraja; (2) To develop characters-based assessments designs which were needed for assessing the characters of tenth grade students of SMKN 3 Singaraja in studying English; (3) To identify the content validity of the developed characters-based assessments; (4) To identify the reliability of the developed characters-based assessments; (5) To identify the problems in implementing the developed characters-based assessments. The data of the study were collected through questionnaire, observation, documentation, expert judgment sheet and test. The collected data were analyzed qualitatively and quantitatively. The results of the study show that: (1) The problems in assessing the studentsâ characters that were faced by the English teachers at SMK N 3 Singaraja were: the difficulty in assessing the studentsâ characters objectively, the difficulty in developing the assessment instrument, the absence of instruments to evaluate the studentsâ characters; (2) The design of the instruments were developed based on the character values that should be integrated in teaching English for Vocational High School students as what are stated on the guideline of character education issued by the curriculum center, and the language skills and the materials that should be covered based on the syllabus; (3) Based on the content validity analysis and empirical validity analysis that have been conducted, it can be concluded that the developed instruments were valid; (4) The reliability analysis of the instruments showed that the instruments were reliable; (5) Some problems were identified during the implementation of the developed instruments, those problems were: time consuming, the difficulty in recognizing the students, and the requirement of high concentration. keyword : assessment, character-based, research and development.